2023
DOI: 10.1101/2023.06.14.23291368
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protein-truncating variants inBSNare associated with severe adult-onset obesity, type 2 diabetes and fatty liver disease

Abstract: Obesity is a major risk factor for many common diseases and has a significant heritable component. While clinical and large-scale population studies have identified several genes harbouring rare alleles with large effects on obesity risk, there are likely many unknown genes with highly penetrant effects remaining. To this end, we performed whole exome-sequence analyses for adult body mass index (BMI) in up to 587,027 individuals. We identified rare, loss of function variants in two genes - BSN and APBA1 - with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…To identify genes associated with either adult BMI or T2D risk, we performed association testing using WGS data available in up to 489,941 UK Biobank participants (see methods). This represents a sample size increase of up to 71,505 individuals compared to our recent WES analyses of the same cohort 9,11 , attributable to both an increase in the number of sequenced samples (N= 35,725) and the inclusion of individuals of non-European ancestry (N= 64,609). Individual geneburden tests were performed by collapsing rare (MAF < 0.1%) variants across 19,457 protein-coding genes.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…To identify genes associated with either adult BMI or T2D risk, we performed association testing using WGS data available in up to 489,941 UK Biobank participants (see methods). This represents a sample size increase of up to 71,505 individuals compared to our recent WES analyses of the same cohort 9,11 , attributable to both an increase in the number of sequenced samples (N= 35,725) and the inclusion of individuals of non-European ancestry (N= 64,609). Individual geneburden tests were performed by collapsing rare (MAF < 0.1%) variants across 19,457 protein-coding genes.…”
Section: Resultsmentioning
confidence: 93%
“…Here, we sought to leverage the increased sample size and purported enhanced capture of rare coding variation from UK Biobank WGS data 7 to provide novel insight into the genetic basis of two cardiometabolic traits of major significance to population health; Type 2 Diabetes (T2D) and Body Mass Index (BMI). Previous large-scale WES studies have identified several genes harbouring rare protein coding variants of large effect for these traits [8][9][10][11][12] including examples where heterozygous loss of function either increases (e.g. GIGYF1 for T2D 13 , BSN for obesity 9,14 ) or decreases the risk of disease (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is inline with personality-and dietary-related variants being expressed in the brain, 13,[42][43][44][45][46] and recent studies have shown the important effect that brain-related variants have on metabolic health outcomes. 47 The only other tissue type enriched in expression among PXS-T2D-associated genes was the pituitary gland.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our lifestyle program allowed the inclusion of patients with CO without a priori suspicion of genetic obesity. Additionally, current obesity gene panels focus on genes causing early‐onset obesity, whereas new literature has suggested that genes such as bassoon presynaptic cytomatrix protein ( BSN ), which is associated with adult‐onset obesity, may play a role as well [28]. Choices had to be made by clinical geneticists with extensive knowledge on genetic obesity regarding which genes to include in the obesity gene panel.…”
Section: Discussionmentioning
confidence: 99%